كفاءة مثبطات التآكل والتكلس لبولي فينيل الكحول المطعم في أنظمة تبريد المياه - موسى المحمد (Tishreen University, 2019)
يعرض هذا البحث نتائج دراسة قدرة مضاد تكلس جديد من البولي فينيل الكحولي (PVA) المطعم بحامض الاكرليك (AAC) وفينيل الأميدازول في حل المشاكل الموجودة في أنظمة تبريد المياه، وتأثير تركيز البوليمير, ودرجة حرارة الماء, وزمن المعالجة في انحلال الفولاذ الكربوني في بيئة مياه تبريد صناعية. وتبين نتائج الدراسة أن البوليمير الجديد بوصفه مضاد تقشر أو تكلس يستطيع أن يخفض نمو بناء القشور تحت ظروف التجربة. إن نسبة انخفاض تشكل القشور باستخدام تركيز PPm 15 من المادة البوليميرية كانت 89 و84 و80% بعد 21 يوماً من حضن المادة مع الماء عند درجات حرارة 30, 70, 95 درجة مئوية على التوالي. كما أن الدراسة تشير إلى أن البوليمر الجديد يعمل مثبطَ تآكل من النوع الأنودي على الفولاذ الصلب، وبالتالي يقلل انحلال المعدن. حيث إن كفاءة تثبيط البولي فينيل الكحولي المطعم وصلت الى 97% عند PPm15 من المادة البوليميرية.   This work presents the results of a study that was undertaken to investigate the ability of a new antiscale, polyvinyl alcohol-grafted-amidazol/acrylic acid in solving problems found in cooling water systems. The effect of the polymer concentration, heat of water and treatment time on C-steel dissolution in synthetic cooling water environment were studied . The results obtained from this study show that the new antiscale polymer can decrease scale build-up growth under experimental Conditions. Percent scale reduction using polymer at 15 ppm concentration was found to be 89%, 84% and 80% after 21 days incubation at 30, 70 and 95°C respectively. The study also indicates that the polymer acted as an anodic type corrosion inhibitor on C-steel, thus reducing metal dissolution. The inhibition efficiency of the grafted polyvinyl alcohol reached to 97% at 15PPm of polymer concentration.